2013
DOI: 10.1149/2.032312jes
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of Bis(3-sulfopropyl) Disulfide and Its Influence on Copper Electrodeposition for Feature Filling

Abstract: The degradation of bis(3-sulfopropyl) disulfide (SPS) during Cu electrodeposition and the influence of its decomposition products on the Cu film properties are investigated. SPS decomposes into 3-mercapto-1-propane sulfonic acid (MPSA) and 1,3-propane disulfonic acid (PDS) by dissociation of the disulfide bond and oxidation reactions. The MPSA seems to recombine to form SPS through a reaction with cupric ions, whereas the PDS accumulates in the plating solution without any further reactions. It was found that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 46 publications
1
32
0
1
Order By: Relevance
“…They found that the overpotential decreased with the addition of SPS, showing that SPS has strong competitive adsorption strength capable of replacing the adsorption sites of PEG. Choe et al [45] studied the degradation behavior of SPS using H-type nuclear magnetic resonance (H-NMR). The results showed that SPS oxidized to 3-mercapto-1-propane sulfonic acid (MPSA) and 1,3-propane disulfonic acid (PDS) in the electroplating process, in which MPSA was able to reconvert to SPS but PDS was not.…”
Section: Acceleratormentioning
confidence: 99%
“…They found that the overpotential decreased with the addition of SPS, showing that SPS has strong competitive adsorption strength capable of replacing the adsorption sites of PEG. Choe et al [45] studied the degradation behavior of SPS using H-type nuclear magnetic resonance (H-NMR). The results showed that SPS oxidized to 3-mercapto-1-propane sulfonic acid (MPSA) and 1,3-propane disulfonic acid (PDS) in the electroplating process, in which MPSA was able to reconvert to SPS but PDS was not.…”
Section: Acceleratormentioning
confidence: 99%
“…From the above results, it was clarified that the sheet resistance value depends not on the crystallite size but on the particle size. Moreover, it has been reported that the increase of crystallite size by annealing is affected by co-deposited carbon, nitrogen and sulfur, which inhibit the growth [18,19]. The crystallite size before annealing of the film prepared by 5 A/dm 2 was about 10 nm as in the case of 50 A/dm 2 .…”
Section: Effects On Electrical Conductivitymentioning
confidence: 94%
“…To meet the requirement of microvia filling, several additives, such as a suppressor, an accelerator or a leveler, must be simultaneously added in the copper plating solution. Currently, bis-(3-sulfopropyl)-disulfide disodium salt (SPS) and its reduction product sodium 3-mercaptopropanesulphonate (Willey and West, 2007;Choe et al, 2013) are widely used as accelerators, and polymeric compounds such as polyethylene glycol (PEG) (Yang et al, 2014), polypropylene glycol (Ryan et al, 2013;Ji et al, 2015aJi et al, , 2015b and their co-polymers (Xiao et al, 2014) are used as suppressors. Leveler is usually a quaternary amine compound or heterocyclic compounds containing nitrogen, such as phenazine dye (Janus Green JGB) and its derivatives such as diazine black and polyalkyl quaternary ammonium salt (polyethyleneimine) (Tsai et al, 2010;Huang et al, 2012).…”
Section: Introductionmentioning
confidence: 99%